Sources of income inequality and poverty in rural Pakistan - Adams, Richard H., Jr.; He, Jane J. (International Food Policy Research Institute, 1995)
Why do some people receive higher incomes than others with similar talents and abilities? And why do certain sources of income, such as income from farm labor and income from growing sugarcane, go to different people? What steps can be taken to reduce the wide differences in income earned, so that the number of people living below the poverty line can be reduced? What roles do education and the migration of household members play in lifting people out of poverty and in improving income distribution? In Sources of Income Inequality and Poverty in Rural Pakistan, Research Report 102, Richard H. Adams, Jr. and Jane J. He address these issues by analyzing longitudinal data from 727 households in four districts in rural Pakistan (Faisalabad and Attock in Punjab Province, Badin in Sind Province, and Dir in North-West Frontier Province). Whereas previous studies of income inequality and poverty have often been based on one round or one year of household interviewing, this data set encompasses 12 rounds of household interviews over a three-year time period, 1986-89. Detailed data were collected on income, expenditures, education, employment, migration, and landowning. Total income is then broken down into 5 sources of income in order to examine the contribution of each of these sources to income inequality and poverty. The report shows that the incomes of poor households fluctuate considerably. When ranked by income data, only one-third of the 145 households in the lowest quintile group in the first year of the study were in that quintile in both of the next two years. This means that most of the poverty found in this study is temporary rather than chronic in nature. Households tend to move in and out of poverty for a variety of reasons. According to this report, changes in physical assets (such as landownership) and the household labor force (through education and migration) account for about one-quarter of the changes in income of the poor.; Why do some people receive higher incomes than others with similar talents and abilities? And why do certain sources of income, such as income from farm labor and income from growing sugarcane, go to different people? What steps can be taken to reduce the wide differences in income earned, so that the number of people living below the poverty line can be reduced? What roles do education and the migration of household members play in lifting people out of poverty and in improving income distribution?To answer these questions, researchers in recent years have used various techniques to analyze the sources of income inequality and poverty in developing countries. These studies help policymakers understand the root causes of income inequality and poverty within their societies. Equipped with such information, policymakers can take specific measures to improve income distribution and the income-earning potentials of different groups of people.